Examining the effects of stroke on students’ L2-grit levels in an EFL context: A case of Northern Iraq - Mohammed, Diyar J. M.; Mohammadzadeh, Behbood; Kılıç, Yalın (Frontiers in Psychology, 2022)
This article investigates the effects of stroke on students’ L2-grit levels in an EFL context in Northern Iraq. A model was created to find how various components such as verbal, non-verbal, valuing, and activities that determine stroke levels affect students’ grit. This study adopted the L2- Grit scale and a language domain-specific grit scale to measure the learners’ L2-grit levels. Also, the Students’ Stroke Scale (SSS) was used to measure the participants’ stroke levels. The study’s sample consisted of 199 participants from various academic levels, undergraduate, graduate, and postgraduate at several Northern Iraq universities. The results reveal a positive and statistically significant association between the score on the L2-Grit scale and the score on the Stroke scale; more specifically, as the scores on the L2-grit scale rise, so do the scores on the Stroke scale. The mean of low stroke is lower than the means of medium stroke and high stroke indicating that as people’s stroke levels grow, so does their L2-grit status. The regression coefficients estimated within the framework of the regression model structured with the logit, the link function, are the same in each category of the dependent variable, satisfying the parallel curves assumption. The overall results show that positive stroke helps learners’ L2-grit levels to arise and lead to a better learning process.